Accurate Modeling and Application of Time-varying Mesh Stiffness of Spur Gear Pair based on Geometry and Potential Energy Method - Wang Xiaopeng; Liu Shijun Li Jiqiang (Jixie chuandong)
Time-varying Mesh Stiffness (TVMS) is one of the important parameter variables in the study of gear system dynamics. It is crucial to accurately simulate TVMS for the analysis of dynamic performance response indexes of gear transmission system such as vibration and noise. On the basis of meshing kinematic equation and geometric position relation of involute gear，one accurate modeling method of spur gear pairs based on geometry and potential energy method is proposed. The meshing limit boundary conditions of standard involute profile is analyzed in real-time and effectively，and a computational analysis model of TVMS from physical model to mathematical model is constructed which combined with the potential energy method. The TVMS of spur gear pair is calculated accurately by numerical calculation method，and an example is given to illustrate its application. On the allowable range of bearing capacity for gear design，it is necessary to select tooth width and shaft diameter reasonably which makes minor adjustments for TVMS. It is also necessary to make further efforts to optimize stiffness and improve anti-deflection performance of rotor system which provide the later stage of gear system dynamics calculation as a basic application research.